Efficacy and Safety of Echinacoside in a Rat Osteopenia Model. (20th March 2013) - Yang, Xiaolin; Li, Fei; Yang, Yanan; Shen, Jinyang; Zou, Run; Zhu, Panpan; Zhang, Chunfeng; Yang, Zhonglin; Li, Ping
Abstract : This study aimed to investigate the efficacy and safety of echinacoside (ECH) using an osteopenia rat model. Forty-eight 6-month-old female Sprague-Dawley rats were randomly divided into one sham-operated group (SHAM) and five OVX (ovariectomized) subgroups: SHAM with vehicle 0.5% carboxymethylcellulose sodium (0.5% CMC-Na) and OVX with vehicle (OVX), OVX with 17 β -estradiol (E2), and OVX with ECH of graded doses (ECH-L, ECH-M, and ECH-H). The effects of ECH and E2 on serum biochemical parameters, bone mineral density (BMD), bone biomechanical properties, bone microarchitecture, and immunohistochemistry were examined, and safety assessments were also evaluated. The results showed that ECH treatments improved total femur BMD, bone microarchitecture, and biomechanical properties and decreased serum marker levels in comparison to OVX group. Moreover, ECH administration significantly increased osteoprotegerin (OPG) level, and decreased receptor activator of nuclear factor- κ B ligand (RANKL) level in serum, as well as in proximal femur. Importantly, ECH treatment ameliorated the lipid parameters without the overall incidences of adverse events of uterus and mammary gland compared to OVX and SHAM groups. This study demonstrated that administration of ECH for 12 weeks can effectively and safely prevent OVX-induced osteoporosis in rats via increasing the OPG/RANKL ratio.